Relationship Between Soil Properties and Nitrogen Mineralization in Undisturbed Soil Cores from California Agroecosystems. Issue 1 (2nd January 2019) - Miller, Kenneth; Aegerter, Brenna J.; Clark, Nicholas E.; Leinfelder-Miles, Michelle; Miyao, Eugene M.; Smith, Richard; Wilson, Rob; Geisseler, Daniel
ABSTRACT: Soil nitrogen (N) mineralization rates from different agricultural regions in California were determined and related to soil properties. Undisturbed soil cores were sampled in spring from 57 fields under annual crop rotations and incubated at 25℃ for 10 weeks. Soil properties varied across and within regions, most notably those related to soil organic matter (SOM), with total soil carbon ranging from 6 to 198 g kg −1 . Multivariate linear regression was used to select soil properties that best predicted N mineralization rates. Regression models with a good fit differed between soils with high and low SOM contents, but generally included a measure of SOM quantity, its quality as well as soil texture or mineralogy. Adjusted R 2 values were 0.95 and 0.60 for high and low SOM soils, respectively. This study has shown that information on soil properties can contribute to better estimates of N mineralization in soils of contrasting characteristics.